Penerapan Model Problem Based Learning dengan Media Wordwall untuk Meningkatkan Motivasi dan Hasil Belajar Siswa Mata Pelajaran Pendidikan Pancasila Materi Keragaman Budaya Indonesia - Nurbiyati, Andri; Permana, Erwin Putera (Jurnal Simki Postgraduate, 2024)
This classroom action research aims to increase the motivation and learning outcomes of Pancasila Education students in Phase C (Class VI) of SD Negeri 3 Cakul, Dongko District, Trenggalek Regency for the 2023/2024 academic year. This research uses the Problem Based Learning (PBL) learning model with Wordwall media on the subject matter of Indonesian Cultural Diversity. The research subjects were 10 students consisting of 4 male students and 6 female students. Inappropriate selection of learning models and media can hinder the achievement of the desired learning goals and outcomes. Another impact is the low reasoning ability of students in learning Pancasila Education. This is because in the teaching and learning process, students are less involved in optimal situations for learning, learning tends to be teacher-centered and classical. By using the Problem Based Learning (PBL) learning model with Wordwall media, it is known that the results obtained are more satisfying because students' learning motivation increases, which results in student learning outcomes also increasing. It is known that in the 2022/2023 academic year, out of 16 students, there were 13 students with a percentage of 81.25% who obtained scores above the KKTP, while 3 other students or a percentage of 18.75% were still below the KKTP. So the researchers concluded that the use of the Problem Based Learning (PBL) learning model with Wordwall media was proven to be able to increase the motivation and learning outcomes of class VI students at SD Negeri 3 Cakul, Dongko District, Trenggalek Regency for the 2023/2024 academic year.